Legend tripping : a contemporary legend casebook - McNeill, Lynne S.; Tucker, Elizabeth, 1948- (University Press of Colorado e-book collection., 2018)
"Explores the practice of legend tripping, where individuals or groups travel to a site where an urban legend is thought to have taken place. Legend tripping is depicted throughout vernacular (contemporary and historical) culture and an expression of humanity's interest in the frontier between life and death"--Provided by publisher.